Ex vivo Expanded Regulatory T cells Combined with Short-term Costimulation Blockade Prevent Rejection of Vascularized Composite Allografts. (July 2018) - Oh, Byoung Chol; Furtmüller, Georg J; Grzelak, Michael; Vuong, Lihn; Iglesias, Marcos; Fryer, Madeline; Cooney, Damon S; Andrew Lee, W.P.; Raimondi, Giorgio; Brandacher, Gerald
Abstract : Background: Reconstructive transplantation represents a valid therapeutic option after devastating tissue loss. Routine clinical application, however, is hampered by the toxicity of long-term maintenance immunosuppression. The current study investigated a novel approach using ex vivo expanded regulatory T cells combined with a short-term immunomodulatory strategy in a murine hind limb transplantation model. Methods: Fully MHC-mismatched orthotopic hind limb transplants were performed from Balb/C to C57BL/6 mice. Recipients in the experimental groups received a combination regimen consisting of 0.5mg CTLA4 Ig on day 0, 2, 4 and 6 post-transplant, 20mg/kg anti-Thy 1.2 mAb on POD-1, and 1mg/kg Rapamycin (POD 0-9), and in one group, 1 wk expanded CD4+CD25+ Treg cells. Allograft survival was monitored and flow cytometric analysis was performed to evaluate mixed chimerism and clonal deletion of alloreactive T cells. Treg activity was assessed in vitro using suppression assays in order to support and supplement in vivo data. Results: Combination of T cell depletion and CTLA4-Ig plus short-course of Rapamycin increased VCA survival significantly while untreated controls rejected allografts (MST 105 days; Untreated, MST 9 days; CTLA4 Ig only, MST 17 days, Rapamycin, MST 20 days; T cell depletion, 20 days; p<0.01[GB1]). [GB2] Mixed chimerism was detected in recipients receiving this combined treatment protocol with 5.013 ± 1.23 % of CD11b+ cells being donor-derived on POD 55. Vβ – TCR staining profiles in recipients after full treatment showed 1.570 ± 0.3700 % of νβ5+CD4+ T cells, while naïve C57BL/6 express 3.567 ± 0.3690 % of νβ5+CD4+ T cells, suggesting the actuation of central deletion of developing donor-reactive T cells. In order to further prolong allograft survival, one week expanded Tregs were then included in the combination therapy. The suppressive activity of the CD4+CD25+ Tregs was confirmed with in vitro suppression assays. The addition of ex vivo expanded regulatory T cells further increased VCA survival to >200 days and induced long-term stable mixed chimerism[GB3] with 16.7±1.5 % of CD11b cells being donor-derived on POD 55 after administration of expanded Treg cells. Conclusion: The combination of T cell depletion, costimulation blockade, and a short-course of Rapamycin prevents VCA rejection and significantly prolongs graft survival without the need for myeloablative conditioning or maintenance therapy. Moreover, regulatory T cells added in the early post transplant period further optimize immune regulation by inducing sustained mixed chimerism.